Seasonal changes in photosynthesis and water-use efficiency of savanna species and eucalypts in Venezuela - Herrera,Ana (2013)
Eucalypt plantations in Venezuela occupy 14% of land covered by savannas. Since water use by plantations in the savannas of Mapire (Venezuelan Llanos) was apparently similar to or lower than in the natural vegetation, evaluating how carbon fixation by plantations compares to the natural vegetation could help to elucidate whether plantations have higher water-use efficiency (WUE) than the savanna. We aimed to determine, using measurements of leaf gas exchange, the seasonal changes in photosynthetic rate (P N) and WUE of a seasonally dry savanna in Mapire, composed mainly of the grass Trachypogon vestitus and the tree Curatella americana, and trees of Eucalyptus urophylla growing in an experimental plantation. Daily integrated WUE (WUEint) was highest in C. americana and similar between T. vestitus and E. urophylla during both seasons. The Gross carbon fixation (GCF) at the leaf level in T. vestitus was similar to C. americana and lower than E. urophylla during the dry season, whereas during the rainy season it was nearly as high as in E. urophylla and both higher than C. americana. Gross carbon fixation (GCF) in T. vestitus was higher than in C. americana, but lower than in E. urophylla during the dry season, while it was much higher than the other two species during the rainy season. The contribution to savanna GCF of C. americana was small and constant throughout the seasons. The GCF in eucalypts was 15% higher than in the savanna during the dry season, but 45% lower during the rainy season, GCF averaging 85% of that in the savanna. Since water use by plantations is lower than in the savanna, they have a large potential for C sequestration without significantly altering ground water availability.